Wholeness in a breaking world: Narratives as sustenance for peace - Miller, M.Z. (2005)
This distinctive collection explores the use of narratives in the social construction of wellness and illness. Narratives, Health, and Healing emphasizes what the process of narrating accomplishes--how it serves in the health communication process where people define themselves and present their social and relational identities. Organized into four parts, the chapters included here examine health narratives in interpersonal relationships, organizations, and public fora. The editors provide an extensive introduction to weave together the various threads in the volume, highlight the approach and contribution of each chapter, and bring to the forefront the increasingly important role of narrative in health communication. This volume offers important insights on the role of narrative in communicating about health, and it will be of great interest to scholars and graduate students in health communication, health psychology, and public health. It is also relevant to medical, nursing, and allied health readers.